Students' extroversion/introversion influences on their oral participation in the advanced intensive english II classroom, semester I - 2013, from the Foreing Languaje Department at The University of El Salvador - Delgado Valenzuela, Ana Isabel
In El Salvador, the learning of English as a foreign language has been increasing more and more in the last years. Nowadays, the english language has become a necessity to the moment of acquiring a new job inside or outside the country and getting involved in the labor world where few people can enter for the lack of this essential tool. However, in the moment of learning a foreign language, students have to face many obstacles from not counting with the necessary economic resources for enrolling in a course to the obstacles in the moment of learning english. Such problems are the fear of committing mistakes the fear of not pronouncing the sounds well, and the fear of not participating in class, among others. This project will be focused on the importance of having an active participation in class and how personality plays an important role in the learning process of a foreign language. Furthermore, this research project seeks to figure out the level of influence that students' personality has on their class participation